Narcolepsy and H1N1 influenza immunology a decade later: What have we learned? - Buonocore, Sofia M.; van der Most, Robbert G. (Frontiers in Immunology, 2022)
In the wake of the A/California/7/2009 H1N1 influenza pandemic vaccination campaigns in 2009-2010, an increased incidence of the chronic sleep-wake disorder narcolepsy was detected in children and adolescents in several European countries. Over the last decade, in-depth epidemiological and immunological studies have been conducted to investigate this association, which have advanced our understanding of the events underpinning the observed risk. Narcolepsy with cataplexy (defined as type-1 narcolepsy, NT1) is characterized by an irreversible and chronic deficiency of hypocretin peptides in the hypothalamus. The multifactorial etiology is thought to include genetic predisposition, head trauma, environmental triggers, and/or infections (including influenza virus infections), and an increased risk was observed following administration of the A/California/7/2009 H1N1 vaccine Pandemrix (GSK). An autoimmune origin of NT1 is broadly assumed. This is based on its strong association with a predisposing allele (the human leucocyte antigen DQB1*0602) carried by the large majority of NT1 patients, and on links with other immune-related genetic markers affecting the risk of NT1. Presently, hypotheses on the underlying potential immunological mechanisms center on molecular mimicry between hypocretin and peptides within the A/California/7/2009 H1N1 virus antigen. This molecular mimicry may instigate a cross-reactive autoimmune response targeting hypocretin-producing neurons. Local CD4+ T-cell responses recognizing peptides from hypocretin are thought to play a central role in the response. In this model, cross-reactive DQB1*0602-restricted T cells from the periphery would be activated to cross the blood-brain barrier by rare, and possibly pathogen-instigated, inflammatory processes in the brain. Current hypotheses suggest that activation and expansion of cross-reactive T-cells by H1N1/09 influenza infection could have been amplified following the administration of the adjuvanted vaccine, giving rise to a "two-hit” hypothesis. The collective in silico, in vitro, and preclinical in vivo data from recent and ongoing research have progressively refined the hypothetical model of sequential immunological events, and filled multiple knowledge gaps. Though no definitive conclusions can be drawn, the mechanistical model plausibly explains the increased risk of NT1 observed following the 2009-2010 H1N1 pandemic and subsequent vaccination campaign, as outlined in this review.